Impact of Robotic-Assisted Electrode Array Insertion on Neural Health and Hearing Outcomes in Cochlear Implant Recipients - Guillaume Gersdorff; Peter Nopp; Severine Camby; Philippe Lefebvre (Audiology and Neurotology, 2026)
Introduction Cochlear implants (CIs) have revolutionized the treatment of severe to profound sensorineural hearing loss, offering significant auditory benefits to individuals who do not benefit adequately from conventional hearing aids. The efficacy of CIs largely depends on the interface between the electrode array and auditory nerve fibers, with neural health playing a crucial role in postoperative outcomes. This study investigates the impact of robotic-assisted electrode array insertion on the preservation of neural health and auditory performance, evaluated through electrically evoked compound action potential (ECAP) measurements and audiometric outcomes. Material and methods A retrospective single-center study was conducted with 20 patients, divided into two groups: manual insertion (n=12) and robotic-assisted insertion (n=8). All patients received Med-El CIs with either FLEX 24 or FLEX 28 electrode arrays. The robotic-assisted insertions were performed using the RobOtol® system. ECAP measurements were taken to assess neural health. Audiometric evaluation using pure-tone audiometry (PTA) was performed preoperatively to confirm group equivalence, while speech intelligibility was assessed both pre- and postoperatively using the auditory capacity index (ACI). Results Robotic-assisted insertion significantly improved neural health preservation, as evidenced by a higher mean ECAP slope difference (2.99 ± 0.69) compared to manual insertion (1.42 ± 0.68), with a significant correlation between ECAP slope difference and speech intelligibility (R2 = 0.23, p=0.032). Additionally, patients in the robotic-assisted group demonstrated superior speech intelligibility scores (ACI: 84.5 ± 11.04%) compared to the manual group (ACI: 69.5 ± 14.29%). Discussion These findings suggest that robotic-assisted cochlear implant surgeries offer substantial benefits in terms of preserving neural health and enhancing auditory outcomes.